NK Cell Exhaustion - Bi, Jiacheng; Tian, Zhigang (Frontiers in Immunology, 2017)
Natural killer cells are important effector lymphocytes of the innate immune system, playing critical roles in anti-tumor and anti-infection host defense. Tumor progression or chronic infections, however, usually leads to exhaustion of NK cells, thus limiting the anti-tumor/infection potential of NK cells. In many tumors or chronic infections, multiple mechanisms might contribute to the exhaustion of NK cells, such as dysregulated NK cell receptors signaling, as well as suppressive effects by regulatory cells or soluble factors within the microenvironment. Better understanding of the characteristics, as well as the underlying mechanisms of NK cell exhaustion, not only should increase our understanding of the basic biology of NK cells, but also could reveal novel NK cell-based anti-tumor/infection targets. Here, we provide an overview of our current knowledge on NK cell exhaustion in tumors, and in chronic infections.